Cuture fibroblasts isolated from mouse tissues - Khanh Hoa, Tran Thi; Duong, Hoang Thuy; Kim Anh, Nguyen Thi (Academia Journal of Biology, 2018)
Fibroblasts are cells which multiple a thounsand times or cultured from the different tissue types with special conditions for each case to obtain the optimal number of cells. This study aims to compare the growth of primary cultured fibroblast cells derived from different tissues of mice and the influence of the replay subculture on cell’s properties, which produce a large sources for biomedical researches. Primary cells were subcultured to maintain cell survival and proliferation. The development ability and cell survival were tested by means of cell counting using Trypan Blue and shapes are observed by 4',6-diamidino-2-phenylindole (DAPI) staining. From the experimental results, cells from the organ are capable of heterogeneous development in a certain time period; simultaneously, to obtain fibroblasts from each tissue type also requires different conditions. Also, study on the influence of the subcultures help to maintain cell life for future experiments.